136k views
4 votes
Evaluate the expression 3x² - 6x given x = -2

1 Answer

2 votes

Answer:

The answer is 48

Explanation:

Evaluating this expression basically means finding the product.
So you input -2 for x in the expression. Which is this one → 3(x)^2 - 6x

Once you input -2 for x it'll look like this ↓

3(-2)^2 - 6(-2)
Now all you have to do is solve and see what number you get! :)

3(-2) = -6

and

6(-2) = -12

so.. it now looks like this ↓

-6^2 - (-12)

and...

-6^2 = -36

so...

-36 - (-12) which equals 48

Kind of long heh- sorry but I hope I helped! :)

User Stofkn
by
4.9k points